2004
DOI: 10.2172/15009631
|View full text |Cite
|
Sign up to set email alerts
|

Avian Monitoring and Risk Assessment at the Tehachapi Pass Wind Resource Area; Period of Performance: October 2, 1996--May 27, 1998

Abstract: UL 18. NUMBER OF PAGES 19b. TELEPONE NUMBER (Include area code) Standard Form 298 (Rev. 8/98) Prescribed by ANSI Std. Z39.18

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Kerlinger 2002; Anderson et al 2004;Kerns et al 2005;Jain et al 2007), which limits and may compromise inference; (2) based on a a priori distribution (exponential distribution) (e.g. Jonhson et al 2003;Erickson et al 2004;Fiedler 2004;Huso 2010), or (3) using estimators not accounting for censored observations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Kerlinger 2002; Anderson et al 2004;Kerns et al 2005;Jain et al 2007), which limits and may compromise inference; (2) based on a a priori distribution (exponential distribution) (e.g. Jonhson et al 2003;Erickson et al 2004;Fiedler 2004;Huso 2010), or (3) using estimators not accounting for censored observations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Searcher Detection I collected data on searcher detection rates from Orloff and Flannery (1992), Kerlinger et al (2000), Johnson et al (2002), Young et al (2003), Anderson et al (2004Anderson et al ( , 2005, Table 1. Unpublished reports of bird collision studies at wind farms in the United States, from which I used data on reported searcher detection and scavenger removal rates.…”
Section: Methodsmentioning
confidence: 99%
“…Wind turbine-caused fatality rates were recently estimated at 2,710 (SE 5 11.848) birds per year in the APWRA, including 1,127 (SE 5 1.547) raptors per year (Smallwood and Thelander 2008). As a result of these high fatality rates, bird mortality has been investigated at other wind farms throughout North America, and bird behaviors and activity levels have been investigated at some of these (Janss and Clave 2000;Kerlinger 2000;Anderson et al 2004Anderson et al , 2005Hoover and Morrison 2005). These investigations attest to the importance attributed to bird behaviors and activity levels in relation to bird collisions with wind turbines.…”
mentioning
confidence: 99%